Unbiased transcriptomic analyses reveal distinct effects of immune deficiency in CNS function with and without injury - Dandan Luo; Weihong Ge; Xiao Hu; Chen Li; Chia-Ming Lee; Liqiang Zhou; Zhourui Wu; Juehua Yu; Sheng Lin; Jing Yu; Wei Xu; Lei Chen; et al. (Protein & Cell, 2018)
Abstract The mammalian central nervous system (CNS) is considered an immune privileged system as it is separated from the periphery by the blood brain barrier (BBB). Yet, immune functions have been postulated to heavily influence the functional state of the CNS, especially after injury or during neurodegeneration. There is controversy regarding whether adaptive immune responses are beneficial or detrimental to CNS injury repair. In this study, we utilized immunocompromised SCID mice and subjected them to spinal cord injury (SCI). We analyzed motor function, electrophysiology, histochemistry, and performed unbiased RNA-sequencing. SCID mice displayed improved CNS functional recovery compared to WT mice after SCI. Weighted gene-coexpression network analysis (WGCNA) of spinal cord transcriptomes revealed that SCID mice had reduced expression of immune function-related genes and heightened expression of neural transmission-related genes after SCI, which was confirmed by immunohistochemical analysis and was consistent with better functional recovery. Transcriptomic analyses also indicated heightened expression of neurotransmission-related genes before injury in SCID mice, suggesting that a steady state of immune-deficiency potentially led to CNS hyper-connectivity. Consequently, SCID mice without injury demonstrated worse performance in Morris water maze test. Taken together, not only reduced inflammation after injury but also dampened steady-state immune function without injury heightened the neurotransmission program, resulting in better or worse behavioral outcomes respectively. This study revealed the intricate relationship between immune and nervous systems, raising the possibility for therapeutic manipulation of neural function via immune modulation.